Condomínio residenciais fechados: um estudo de caso no município de Itu-SP - Savioli, Giovanna Fioravanti [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
Since the middle of the XX century, observed a guided development in capitalism and globalization. In this context, a new way of thinking and producing dwellings, closed horizontal residential condominiums, with its beginnings in the United States. Currently, these also appear as a trend in Brazil. Their deployment has generated both social and spatial problems, since the production and consumption of urban space are given in different ways in different social classes. This process began in the 1970s and was unique to metropolitan areas until the 1980s, when it began to achieve medium-sized cities. Thus, highlighting some points, such as the production and consumption of urban space and the construction of condominiums in average Brazilian cities, this paper aims to describe and analyze the dynamics of residential condominiums in the city of Itu (SP)

Desde meados do século XX, observamos um desenvolvimento pautado no capitalismo e na globalização. Sob este contexto, surge uma nova maneira de pensar e de produzir habitações, os condomínios residenciais horizontais fechados, tendo o seu início nos Estados Unidos. Atualmente, estes também aparecem como tendência no Brasil. A sua implantação tem gerado problemas tanto sociais quanto espaciais, uma vez que a produção e o consumo do espaço urbano se dão de maneiras diferentes nas diversas classes sociais. Este processo teve início na década de 1970, tendo sido exclusivo as regiões metropolitanas até a década de 1980, quando começou a atingir as cidades médias. Assim, ressaltando alguns pontos, como a produção e o consumo do espaço urbano e o processo de construção de condomínios em cidades médias brasileiras, este trabalho pretende descrever e analisar a dinâmica dos condomínios residenciais na cidade de Itu (SP)
Keywords: Geografia urbana; Urbanização; Segregação urbana; Condomínios; Conjuntos habitacionais; Itu (SP)